Flexural Performance of a New Composite Double PSSDB Slab System Filled with Recycled Concrete - Al-Sudani, Zaid A.; De’nan, Fatimah; Al-Zand, Ahmed W.; Abd Rahman, Noorhazlinda; Liejy, Mohammed C. (Civil Engineering Journal, 2024)
This study investigated the flexural performance of a composite floor system utilizing a profile steel sheet dry board (PSSDB) that was enhanced by adding an additional layer of profile steel sheet (PSS) and infilled with both normal and recycled concrete materials. This improved system is referred to as the double-profile steel sheet dry board (DPSSDB) system. The new DPSSDB concept was proposed to reduce fabrication costs, overall weight, and the depth of the composite floor system compared to traditional composite beam-slab systems. To assess the impact of the additional PSS layer, ten full-scale specimens of both PSSDB and DPSSDB were subjected to four-point static load tests. Additionally, the study investigated the use of lightweight recycled aggregates such as crumb rubber and expanded polystyrene as partial replacements for the aggregates in the infill concrete. The results demonstrated that the DPSSDB system exhibited a 112–170% increase in bending capacity compared to the PSSDB specimens. Partial replacement of concrete aggregates with lightweight recycled materials up to 50% had only a marginal effect on the bending behavior of both PSSDB and DPSSDB specimens compared to those filled with normal concrete. However, replacing 75% of the aggregate with recycled materials led to a 27% reduction in the flexural bending capacity of the DPSSDB specimens compared to those infilled with normal concrete. Additionally, a new method (theoretical equation) was developed to predict the ultimate moment strength (flexural) of the novel DPSSDB composite slab system, which aligned well with the experimental results, achieving a deviation percentage of 0.81% and a mean value of 0.965a. Doi: 10.28991/CEJ-2024-010-12-03 Full Text: PDF